The Influence of Information and Communication Technology (ICT) Skill and Work Culture on Teacher Performance at SMP Negeri Bangkinang Kampar - Maulina, Fahni; Suanto, Elfis; Hambali, Hambali (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
Teacher performance is something that needs and deserves to be examined in depth. Many factors cause problems related to teacher performance. This article covers the influence of information and communication technology (ICT) skills and work culture on the performance of state junior high school teachers in the Bangkinang districts of Kampar. This research uses a quantitative-descriptive approach. The quantitative-descriptive research systematically, actually, and accurately describes certain social phenomena to describe the existing facts and data in detail. Data collection techniques use observation, documentation, and questionnaires. The subjects of the research were 55 teachers at state junior high schools in Bangkinang. The results show that 1) information and communication technology (ICT) skill has a significant positive influence on teacher performance with a significance value of 0.002 or smaller than the alpha value of 0.05. In addition, 2) work culture has a significant positive influence on teacher performance with a significance value of 0.001. And, 3) information and communication technology (ICT) skill and work culture have a joint influence on teacher performance with a significance value of 0.000 and an R-square value of 0.403, which indicates that the proportion of influence of the variables information and communication technology (ICT) skill and work culture on teacher performance is 40.3%.